Technical issues in quantifying low-frequency fatigue in athletes - Fowles, J. R. (International Journal of Sports Physiology and Performance, 2006)
A recent review by Cairns and colleagues published in Exercise and Sport Sciences Reviews (2005:33[1]:9-16)1 described experimental models used to study neuromuscular fatigue and explained the inherent strengths and weaknesses of applied versus reductionist approaches. This technical report addresses some of the recommendations made in that review, from the perspective of the applied sport scientist or practitioner in evaluating fatigue in elite athletes. The goal here is to highlight the inherent difficulties in assessing fatigue in the applied sport setting and to provide practitioners with future directions for fatigue research. A particular type of fatigue, called low-frequency fatigue (LFF), is of particular interest to the applied sport scientist or practitioner and could be the focus of future work. This report identifies some of the technical challenges faced in developing a practical test of LFF for use in the field setting. The outcome of further work in this area will lead to a better understanding of athlete monitoring, training, and performance.